Appropriateness of intravenous fluid prescriptions in hospitalised patients: a point prevalence study - Sneyers, Barbara; Nyssen, Caroline; Bulpa, Pierre; Michaux, Isabelle; Lacrosse, Dominique; Dubois, Philippe E.; Rotens, Thomas; Spinewine, Anne (International journal of clinical pharmacy, 2025)
Background Inappropriate use of intravenous (IV) fluids results in fluid overload, electrolyte disturbances, and increased costs. Aim To describe IV fluid prescribing and its appropriateness in hospitalised patients. Method A point prevalence study was conducted at two sites (academic and general) of a tertiary care hospital in Belgium. All inpatients (except those in the operating theatre) and all IV fluids prescribed during a 24-h period were analysed. Data collected included type, rate and volume administered. Each IV fluid was classified by indication (i.e., resuscitation/replacement, maintenance, catheter patency management, drug administration). Appropriateness was assessed using predefined criteria and validation by attending clinicians. Results IV fluids were administered to 60% (297) of patients, with a median of 3 [IQR 0.5–6] IV fluid bags per patient and a median daily volume of 1000 ml [IQR 100–1550]. Amongst the 1162 IV fluid prescribed bags, 61.2% (712) were for drug administration, 22.1% (257) for catheter patency, 9.7% (112) for maintenance and 7.1% (82) for replacement/resuscitation. Inappropriate use was found for 56.9% (169) of patients with an IV fluid, representing a median volume of 300 ml per patient [IQR 10–500], and median costs of 4.60 € per patient [IQR 0.4–6.7]. Conclusion Inappropriate IV fluid use is frequent in hospitalised patients, and results in significant costs. Optimisation strategies are needed.